Outdoor Study for Understanding and Critical Thinking Skills of Rock Material (Geosite) Karangsambung – Karangbolong Geopark - Ni'am Khakiki; Dewi Liesnoor Setyowati; Puji Hardati; Hariyanto Hariyanto; Erni Suharini (Universitas Negeri Semarang, 2025)
Geography learning has not utilized the potential of the Karangsambung - Karangbolong Geopark geosite as a learning resource. The purpose of this study is to analyze the implementation of outdoor study and evaluate understanding and critical thinking skills after studying rock material in the Karangsambung - Karangbolong Geopark. The research design was Pre-Experimental Design, and One Shoot Case Study approach. The sample of class X 1 was 34 students and 4 geosite. Data collection used observation, interviews, documentation studies, student worksheets, questionnaires and test. Data analysis used descriptive and scoring. The results of the outdoor study in the Karangsambung - Karangbolong Geopark made it easier for students to identify rocks in the field 58,82% (high) and 41,18% (moderate). Students positive responses that outdoor study made it easier and helped them understand rock material 52,90% (aappropriate) and 47,10% (very appropriate). Outdoor study at the Karangsambung - Karangbolong Geopark supported student understanding with 52,94% (high), 35,29 (moderate) and 11,76 (sufficient). Meanwhile, students critival thinking skills average 36 (high) with 50% hight and 50% (moderate).